ANALISIS PROFESIONALISME AUDITOR INTERNAL PADA PT SWADAYA MAKASSART DI MAKASSAR - Astuty Hasti; Panji Permadi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
Professionalism is the credibility of an internal auditors and the professionalism of internal auditors is one of the success keys in carrying out their duties. Internal auditors are required to be able to carry out their audit duties seriously and their application must be consistent with the norms of the practice of professional auditors.This study aims to determine the professionalism of internal auditors at PT. Swadaya Makassart. The research method used is a qualitative descriptive method where there is only one variable and does not make a comparison.Based on the results of the study it can be concluded that the professionalism of existing internal auditors is good enough, referring to the results of measurements of independence, professional expertise, and compliance with the code of ethics.